Kebijakan Kriminal dalam Penanganan Siber di Era Digital: Studi Kasus di Indonesia - Arafat, Muhammad; Alexander Tito Enggar Wirasto (Equality : Jurnal Hukum dan Keadilan, 2024)
Digital technology in Indonesia has significantly impacted sectors such as government, finance, education, and healthcare, offering numerous benefits. However, it has also led to increased cybercrime, including hacking, digital fraud, identity theft, and ransomware, posing threats to national security and public welfare. Regulations like the ITE and PDP Laws have been implemented, yet challenges persist in enforcement and technological adaptation. Indonesia faces challenges in cyber law enforcement, including insufficient technical capacity among law enforcement officers. This study employs a qualitative descriptive approach with an exploratory focus. Data were collected from legal documents, government reports, case studies, journal articles, and academic literature. Thematic analysis was used to identify patterns, challenges, and the effectiveness of cybercrime policies. The findings reveal that Indonesia’s cybersecurity policies need reinforcement, particularly in implementation, public education, and technological adaptation. Examples from the United States and the European Union highlight that collaboration between governments and the private sector, stringent data protection regulations, and public education campaigns significantly enhance resilience against cyber threats. This study recommends strengthening the ITE and PDP Laws, promoting digital literacy among the public, enhancing law enforcement capacities, fostering international collaboration, and establishing cyber information-sharing networks to create a robust, effective, and adaptive digital security ecosystem for Indonesia.